Building information modelling: general overview - Hassan А.; Donenko, V. (Ways to Improve Construction Efficiency, 2019)
This article presents a quick review for Building Information Modeling (BIM) in the past and the anticipated benefits in the future and why BIM is considered as an intelligent model and why we have to use BIM as our concept by explaining how BIM goes further than traditional cad drawings. The selection of suitable Architectural Software is discussed.